Evaluation of the persistence of transformation products from ozonation of trace organic compounds – A critical review. (1st January 2015) - Hübner, Uwe; von Gunten, Urs; Jekel, Martin
Abstract: Ozonation is an efficient treatment system to reduce the concentration of trace organic compounds (TrOCs) from technical aquatic systems such as drinking water, wastewater and industrial water, etc. Although it is well established that ozonation generally improves the removal of organic matter in biological post-treatment, little is known about the biodegradability of individual transformation products resulting from ozonation of TrOCs. This publication provides a qualified assessment of the persistence of ozone-induced transformation products based on a review of published product studies and an evaluation of the biodegradability of transformation products with the biodegradability probability program (BIOWIN) and the University of Minnesota Pathway Prediction System (UM-PPS). The oxidation of TrOCs containing the four major ozone-reactive sites (olefins, amines, aromatics and sulfur-containing compounds) follows well described reaction pathways leading to characteristic transformation products. Assessment of biodegradability revealed a high sensitivity to the formed products and hence the ozone-reactive site present in the target compound. Based on BIOWIN, efficient removal can be expected for products from cleavage of olefin groups and aromatic rings. In contrast, estimations and literature indicate that hydroxylamines and N-oxides, the major products from ozonation of secondary and tertiary amines are not necessarily better removed in biological post-treatment. According to UM-PPS, degradation of these products might even occur via reformation of the corresponding amine. Some product studies with sulfide-containing TrOCs showed a stoichiometric formation of sulfoxides from oxygen transfer reactions. However, conclusions on the fate of transformation products in biological post-treatment cannot be drawn based on BIOWIN and UM-PPS. Graphical abstract: Highlights: Review of product studies from the reaction of ozone with trace organic compounds. Evaluation of the biodegradability of transformation products with different tools. Results suggest enhanced removal by cleavage of olefin groups and aromatic rings. Major products from ozonation of amines are not necessarily better biodegradable.